Features of photonuclear radionuclide production in the thick targets - Torgovkin, A.V. (Вопросы атомной науки и техники, 2015)
One of the basic requirements for the production technology of radionuclides is to provide a high specific activity of the target nuclide as well as its full activity in target. Traditionally this problem is solved by using a large volume of photonuclear targets with subsequent by radiochemical separation target nuclide. Modeling and experimental study of the spatial distribution of the activity carried out in this work for the various targets. Optimal parameters of irradiation to achieve the maximum yield of isotopes Мо⁹⁹(Тс⁹⁹m) and Сu⁶⁷ in targets from molybdenum and zinc of natural composition have been found.